Prognosis of Adults With Isolated Left Ventricular Non-Compaction: Results of a Prospective Multicentric Study - Gerard, Hilla; Iline, Nicolas; Martel, Hélène; Nguyen, Karine; Richard, Pascale; Donal, Erwan; Eicher, Jean-Christophe; Huttin, Olivier; Selton-Suty, Christine; Raud-Raynier, Pascale; Jondeau, Guillaume; Mansencal, Nicolas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Whether left ventricular non-compaction (LVNC) bears a different prognosis than dilated cardiomyopathy (DCM) is still a matter of debate. Methods: From a multicenter French prospective Registry, we compared the outcomes of 98 patients with LVNC and 65 with DCM. The primary endpoint combined cardiovascular death, heart transplantation and hospitalisation for cardiovascular events. The two groups presented similar outcome but different left ventricular ejection fraction (LVEF), (43.3% in LVNC vs 35.95% in DCM, p = 0.001). For this reason, a sub-group analysis was performed comparing only patients with LVEF ≤ 45%, including 56 LVNC and 49 DCM. Results: Among patients with LVEF≤ 45%, at 5-year follow-up, the primary endpoint occurred in 33 (58.9%) among 56 LVNC and 18 (36.7%) among 49 DCM patients (p = 0.02). Hospitalization for heart failure (18 [32.14%] versus 5 [10.20%], p=0.035) and heart transplantation were more frequent in the LVNC than in the DCM group. The incidences of rhythmic complications (24[42.85%] versus 12 [24.48%], p=0.17), embolic events and cardiovascular death were similar between LVNC and DCM. Among the 42 patients with LVNC and LVEF > 45%, the primary endpoints occurred in only 4 (9.52%) patients, including 2 hospitalizations for heart failure, 3 rhythmic complications, but no embolic events. Conclusions: In this prospective cohort, LVNC patients with left ventricular dysfunction present a poorer prognosis than DCM patients. Heart failure events were especially more frequent but embolic events were not. Patients with LVNC and preserved ejection fraction present very few events at 5-year.